2012
DOI: 10.1128/aem.06671-11
|View full text |Cite
|
Sign up to set email alerts
|

Validating Thermal Inactivation of Salmonella spp. in Fresh and Aged Chicken Litter

Abstract: Our results revealed that a 7-log reduction of Salmonella can be achieved by exposing fresh chicken litter for 80.5 to 100.8, 78.4 to 93.1, and 44.1 to 63 min at 70, 75, and 80°C, respectively, depending on initial moisture contents. However, the aged chicken litter requires more heat treatment.A pproximately 14 million tons of poultry litter, most of which was broiler litter (68%), was produced on U.S. poultry farms in 1990, and over 90% of poultry litter is applied to agricultural land (22). However, the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 27 publications
2
51
0
6
Order By: Relevance
“…The authors observed that the aerobic and anaerobic microbial counts could be significantly reduced if the moisture content of the sample was reduced to less than 10%. Kim et al (2012) studied the thermal inactivation of Salmonellae in broiler litter by dry heat and found that the temperature and moisture content affected the survival of Salmonellae in the litter. They reported the time required for a 7 log reduction in Salmonellae at 30% moisture content to be 80, 78 and 44 min for the 70, 75 and 80°C drying conditions respectively.…”
Section: ×10mentioning
confidence: 99%
“…The authors observed that the aerobic and anaerobic microbial counts could be significantly reduced if the moisture content of the sample was reduced to less than 10%. Kim et al (2012) studied the thermal inactivation of Salmonellae in broiler litter by dry heat and found that the temperature and moisture content affected the survival of Salmonellae in the litter. They reported the time required for a 7 log reduction in Salmonellae at 30% moisture content to be 80, 78 and 44 min for the 70, 75 and 80°C drying conditions respectively.…”
Section: ×10mentioning
confidence: 99%
“…However, chicken litter may contain loads of human pathogens, such as Salmonella spp., that have great potential to directly or indirectly contaminate fresh produce and cause food-borne disease outbreaks (1). Currently, high-temperature processing is the most commonly applied method to reduce or eliminate potential pathogens in chicken litter (1,4).…”
mentioning
confidence: 99%
“…However, some pathogenic cells may become acclimatized to hostile environments during stockpiling or composting, which can cross-protect them against subsequent thermal treatment (1, 7). A limitation regarding most published thermal inactivation studies on pathogens in compost and manure is that the conclusions are primarily based on using nonstressed cells (5,6), and the data obtained from these studies can be misinformed or biased. Currently, the use of stressed cells in the challenge studies on validating the efficacy of heat-based hurdles for food-borne pathogens is still novel, and few examples of quantitative assessments are available in the published literature (8,9).…”
mentioning
confidence: 99%
“…Notably, chicken litter is a heterogeneous waste product with variable compositions and differences in physical, chemical, and microbiological properties, which can be affected by storage time and other factors (6). In addition to composting, physical dry-heat treatment after composting or without composting is one of the most commonly used methods to eliminate potential pathogens in chicken litter (6). The storage time of chicken litter may, to some extent, affect the thermal inactivation of food-borne pathogens.…”
mentioning
confidence: 99%
See 1 more Smart Citation